Dentition status in relation to nutritional condition among a group of intermediate school students in Al-Najaf city / Iraq - Hadi Laith, Noor M; Al-Rawi, Nadia A (Journal of Baghdad College of Dentistry, 2017)
Background: Nutrition can affect the development and integrity of the oral cavity as well as the progression of oral diseases such as dental caries which was the most predominant and wide spread not life threatening human diseases especially in developing countries as in Iraq. This study was conducted to assess the occurrence, prevalence and severity of dental caries condition and their relations to nutritional status among intermediate schools females in Al-Najaf city in Iraq. Materials and methods: This study was conducted among intermediate schools females aged 13, 14 and15 years old and the total sample consisted of 754 students. The assessment of nutritional status was performed using body mass index (BMI) following Centers for Disease Control and Prevention growth chart (2000). Diagnosis and recording of dental caries was according to the criteria of WHO 1987.Results: The percentage of well-nutrition was (96.2%) while the prevalence of malnutrition was (3.8%). Result showed that only 5.17% of the total sample was caries-free. The mean dmft for deciduous teeth was equal to (1.77±0.15) and dmfs (3.92±0.39), while concerning permanent teeth the mean DMFT was equal to (4.68±0.10) and DMFS (6.22±0.16), significant differences were seen between DMFT, DMFS and age while opposite was found with nutritional status, and no significant differences were seen between caries experience of primary teeth and age and this similar was found with nutritional statusConclusion: This study revealed that a higher prevalence of dental caries among well-nourished females students aged 13-15 years. Therefore, there is need for an improving public and school preventive programs, and encouraged to orient health knowledge in a positive direction.